Clinical and pathogenetic role of immunoinflammatory activation and endothelial dysfunction in patients with coronary heart disease associated with hypothyroidism based on the results of cognitive modeling - Mykhailovska, N. S.; Oliynyk, T. V.; Михайловська, Наталія Сергіївна; Олійник, Тетяна Вікторівна (Zaporizhzhya state medical university, 2017)
Objective – to study the relationship between the level of thyroid hormones and clinical, autonomic, structural and functional characteristics of heart affections, activity of immune inflammation markers, endothelial dysfunction by means of cognitive modeling. Methods. 60 patients with coronary heart disease with concomitant hypothyroidism were examined (the average level of TSH 13.05 ± 3.30 mU/ml, the average level of FT4 11.45 ± 0.72 pmol L, the average age of patients – 60.5 (54.0; 64.5) years, among them 16 (27 %) were men and 44 (73 %) women. The complex clinical examination including clinical, biochemical, immune-enzyme and instrumental methods of examination, correlation and regression analysis of the data was carried out. Results. The correlation analysis showed that in patients with coronary heart disease, comorbid with hypothyroidism, the reduction of left ventricular ejection fraction was mostly associated with the increasing levels of neopterin and tumor necrosis factor-α (r = -0.37 and r = -0.38 respectively; p < 0.05); condition of myocardial stiffness correlated with the concentration of C-reactive protein (r = +0,56; p < 0,05); level of total cholesterol (TС) – with concentration of neopterin (r = +0.39; p < 0.05) and plasminogen activator inhibitor-1 (PAI-1) (r= +0.50; p < 0.05); heart rate variability parameters and indicators of myocardial ischemic changes correlated with the level of neopterin and endothelin-1. The value of FT4 had a correlation with the concentration of neopterin (r = -0.34; p < 0.05) and PAI-1 (r = -0.52; p < 0.05), left ventricular myocardium mass index (LVMI) (r =-0.44; p < 0.05), early and late diastolic filling velocities of the left ventricle and their ratio (r = +0.50, r = -0,42 and r = -0.41, respectively, p <0.05), standard deviation of normal-to-normal intervals (SDNN) in the active (r = +0.45; p < 0.05) and passive (r = +0.36; p < 0.05) periods, ТС (r = -0.33; p < 0.05). The performed regression analysis confirmed the direction of relations, also allowed to build the cognitive model of the clinical course of ischemic heart disease in patients with hypothyroidism, where the FT4 acts as a connecting link. Conclusions. The cognitive model developed on the basis of correlation and regression analyzes demonstrates clinical and pathogenetic role of immune inflammation markers and endothelial dysfunction in the progression of structural and functional heart disorders, ischemic and autonomic changes in CHD patients with concomitant hypothyroidism, where FT4 level acts as a connecting link. Мета роботи – дослідження взаємозв’язків між рівнем гормонів щитоподібної залози та клінічними, вегетативними, структурно-функціональними особливостями ураження серця, активністю маркерів імунного запалення, ендотеліальної дисфункції шляхом когнітивного моделювання. Матеріали та методи. Обстежили 60 хворих на ішемічну хворобу серця з супутнім гіпотиреозом (середній рівень ТТГ – 13,05 ± 3,30 мкМО/мл; середній рівень Т4 вільний – 11,45 ± 0,72 пМоль/л, медіана віку хворих – 60,5 (54,0; 64,5) років, серед них 16 (27 %) чоловіків та 44 (73 %) жінки. Здійснили комплексне клінічне обстеження з використанням загальноклінічних, біохімічних, імуноферментних та інструментальних методів обстеження; кореляційний і регресійний аналіз даних. Результати. Кореляційний аналіз показав: у хворих на ішемічну хворобу серця, що коморбідна з гіпотиреозом, зниження фракції викиду лівого шлуночка найсуттєвіше асоціювалось зі зростанням рівня неоптерину та фактора некрозу пухлини-α (r = -0,37 та r = -0,38 відповідно; р<0,05); стан жорсткості міокарда корелював із концентрацією С-реактивного білка (r = +0,56; р < 0,05); рівень загального холестерину (ЗХС) – із концентраціями неоптерину (r = +0,39; р < 0,05) та інгібітора тканинного активатора плазміногену-1 (ІТАП-1) (r = +0,50; р < 0,05); параметри варіабельності серцевого ритму та індикатори ішемічних змін міокарда мали взаємозв’язок із рівнем неоптерину та ендотеліну-1. Концентрація Т4 вільного найсуттєвіше корелювала з рівнями неоптерину (r = -0,34; р < 0,05) та ІТАП-1 (r = -0,52; р < 0,05), індексом маси міокарда (r = -0,44; р < 0,05), швидкістю раннього та пізнього діастолічного наповнення лівого шлуночка, а також їхнім співвідношенням (r = +0,50, r = -0,42 та r = -0,41 відповідно, р < 0,05), стандартним відхиленням NN інтервалів за активний (r = +0,45; p < 0,05) і пасивний (r = +0,36; p < 0,05) періоди, ЗХС (r = -0,33; р < 0,05). Регресійний аналіз показав спрямованість виявлених взаємозв’язків, а також дав можливість побудувати когнітивну модель перебігу ішемічної хвороби серця у хворих із гіпотиреозом, де рівень Т4 вільного виступив сполучною ланкою. Висновки. Когнітивна модель, що розроблена на підставі кореляційного та регресійного аналізів, доводить клініко-патогенетичну роль маркерів імунного запалення та ендотеліальної дисфункції у прогресуванні структурно-функціональних порушень серця, ішемічних і вегетативних змін у хворих на ІХС із супутнім гіпотиреозом, де рівень Т4 вільного є сполучною ланкою.
Клініко-патогенетична роль імунозапальної активації та ендотеліальної дисфункції у хворих на ішемічну хворобу серця, що асоційована з гіпотиреозом, за результатами когнітивного моделювання
Keywords: coronary disease; hypothyroidism; biological markers; lipids; cardiac remodeling; myocardial ischemia; statistical model; ішемічна хвороба серця; гіпотиреоз; біологічні маркери; ліпіди; ремоделювання серця; ішемія міокарда; статистична модель